Green Constitution In Government Supervision of Mining Activities - Mangawe, Darmawan Arung Pryantomo; Saptenno, Marthinus Johanes; Pietersz, Jemmy Jefry (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: This article analyzes the concept of Green Constitution, which is essentially the idea of sustainable environmental development. The eco-friendly concept itself is more of a method rather than a status, more of a verb rather than an adjective.Purposes of the Research: The purpose of this article is to understand and analyze the concept of Green Constitution in the management of mining resources, as well as the government's supervisory responsibility over mining activities based on the Green Constitution concept.Methods of the Research: In conducting this research, the author employs a normative juridical legal research method. Juridical research refers to examining legal aspects based on legislation, while normative research is legal research aimed at finding legal rules and doctrines to address existing legal issues.Results Main Findings of the Research: Based on the findings of existing research, the Green Constitution functions as a critique of interests that only prioritize economic benefits over the environment. As a result of regulations that do not fully uphold the Green Constitution, there is an impact on the weak supervision from the government over mining activities.